Endometrial Cancer: Comparison of Patients with Synchronous Primary Carcinoma of the Endometrium and Ovary vs. Endometrial Carcinoma with Ovarian Metastases - Juhasz-Böss, I.; Fehm, T.; Becker, S.; Rothmund, R.; Krämer, B.; Staebler, A.; Wallwiener, D.; Solomayer, E. F. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: The aim of our study was to investigate the rate of secondary carcinomas in patients with endometrial carcinoma (EC). In particular, we wanted to describe the subset of patients with endometrial and simultaneous ovarian carcinoma (OC), including outcomes. The study also compared patients with EC and ovarian metastasis with patients with EC and simultaneous OC. Patients and Methods: Data from 251 patients with primary endometrial carcinoma who underwent surgery in the years 2005–2009 at the Department of Obstetrics and Gynaecology, University of Tübingen, were analysed retrospectively. Results: A total of 28 patients (11.1 %) had a secondary carcinoma: 18 patients (7.1 %) had OC; 9 (3.5 %) patients had a history of breast cancer, and one patient (0.4 %) respectively had simultaneous carcinoma of the vulva or bladder. 14 patients (5.5 %) had advanced stage EC with ovarian metastasis or, in one case, metastasis to the ovarian tube. Patients with ovarian metastasis had a mean age of 71.2 ± 9.2 years at primary diagnosis, making them significantly older compared to patients with EC and simultaneous OC (55.3 ± 11.8 years, p < 0.001). Moreover, patients with ovarian metastasis significantly more often had EC with a higher tumour grade (grade 1: 0, grade 2: 21.4 %, grade 3: 78.6 %) compared to patients with simultaneous EC and OC (grade 1: 11.1 %, grade 2: 77.8 %, grade 3: 11.1 %; p < 0.001). Conclusion: Almost one in 10 patients with EC had a secondary carcinoma. The most common secondary carcinoma was OC followed by breast cancer. This should be taken into account in the diagnosis and therapy of patients with EC. Patients with simultaneous EC and OC were significantly younger than patients with EC and ovarian metastasis. In addition, their tumour had better prognostic features: thus, the tumour grade of the EC was significantly lower. Overall, the prognosis for patients with synchronous EC and OC is better than that for patients with EC and ovarian metastasis.
Keywords: synchronous carcinomas; endometrial cancer; ovarian cancer; ovarian metastases; outcome